ANALISIS KEPRIBADIAN TOKOH UTAMA KATORI MASAKO DALAM NOVEL “OUT” KARANGAN NATSUO KIRINO -PENDEKATAN MENGGUNAKAN PSIKOLOGI ANALITIK C.G JUNG- - Wardhani, Lia Kusuma (Jurnal Ilmiah Mahasiswa FIB, 2013)
Novel can be analyzed with phsycology approach to knowing about the characters’s personality, especially main character. Personality is the behavior which conscious nor unconscious and have uniqe characteristics. One of the theory to knowing main character’s personality is analitic phsychology theory which  stated by C.G Jung. This theory suggest that there are four important aspects of human personality development, include : (1) Persona, (2) Shadow, (3) Anima dan Animus, and (4) Self. Novel “OUT” is selected in this research because full of the emotion which can describe the characters’s phsychology condition and enable to be studied with C.G Jung’s analytic phsychology theory.The conclusion from the analysis conducted are the main character, Masako Katori, (1) can portray the flexible persona. This is makes her can socializing with the neighborhood very well. She is the character with nice “mask.” (2) Masako has strong shadow. This is makes her can mutilites Kenji’s corpse, The old man’s corpse, her friend Kuniko, and kills Satake who yakuza want to kill her. (3) Based on Jung’s anima and animus, Masako is androgyny, who has strong feminine and maskuline characteristic. (4) Self in Masako is be explained that she stills processing to search her identity.